![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
phân tích đa thức thành nhân tử
a) 4x^2+8xy-3x-6y
b)x^4y-3x^3y^2+3x^2y^3+xy^4
c)x^3-5x^2-14x
d)x^4+4y^4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(4x^2+8xy-3x-6y=4x\left(x+2y\right)-3\left(x+2y\right)=\left(4x-3\right)\left(x+2y\right)\)
\(x^4y-3x^3y^2+3x^2y^3-xy^4=xy\left(x^3-3x^2y+3xy^2-y^3\right)=xy\left(x-y\right)^3\)
\(x^3-5x^2-14x=x\left(x^2-5x-14\right)=x\left(x^2-7x+2x-14\right)=x\left[x\left(x-7\right)+2\left(x-7\right)\right]=x\left(x-7\right)\left(x+2\right)\)
\(x^4+4y^4=\left(x^2\right)^2+2\times x^2\times2y^2+\left(2y^2\right)^2-4x^2y^2=\left(x^2+2y^2\right)^2-\left(2xy\right)^2=\left(x^2-2xy+2y^2\right)\left(x^2+2xy+2y^2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
6x^3 + x + 4 = 11x^2
<=>6x3-11x2+x+4=0
<=>6x3+3x2-14x2-7x+8x+4=0
<=>3x2(2x+1)-7x(2x+1)+4(2x+1)=0
<=>(2x+1)(3x2-7x+4)=0
<=>(2x+1)(3x2-3x-4x+4)=0
<=>(2x+1)(3x-4)(x-1)=0
<=>2x+1=0 hoặc 3x-4=0 hoặc x-1=0
<=>x\(\in\){-1/2;1;4/3}
b)x^6 - 14x^4 + 49x^2 = 36
<=>x6-14x4+49x2-36=0
<=>x6-x4-13x4+13x2+36x2-36=0
<=>x4(x2-1)-13x2(x2-1)+36(x2-1)=0
<=>(x2-1)(x4-13x2+36)=0
<=>(x+1)(x-1)(x4-9x2-4x2+36)=0
<=>(x+1)(x-1)[x2(x2-9)-4(x2-9)]=0
<=>(x-1)(x+1)(x2
-9)(x2-4)=0
<=>(x-1)(x+1)(x+3)(x-3)(x+2)(x-2)=0
<=>x\(\in\){-3;-2;-1;1;2;3}
p/s: kham khảo
![](https://rs.olm.vn/images/avt/0.png?1311)
6x^3 + x + 4 = 11x^2
<=>6x3-11x2+x+4=0
<=>6x3+3x2-14x2-7x+8x+4=0
<=>3x2(2x+1)-7x(2x+1)+4(2x+1)=0
<=>(2x+1)(3x2-7x+4)=0
<=>(2x+1)(3x2-3x-4x+4)=0
<=>(2x+1)(3x-4)(x-1)=0
<=>2x+1=0 hoặc 3x-4=0 hoặc x-1=0
<=>x\(\in\){-1/2;1;4/3}
b)x^6 - 14x^4 + 49x^2 = 36
<=>x6-14x4+49x2-36=0
<=>x6-x4-13x4+13x2+36x2-36=0
<=>x4(x2-1)-13x2(x2-1)+36(x2-1)=0
<=>(x2-1)(x4-13x2+36)=0
<=>(x+1)(x-1)(x4-9x2-4x2+36)=0
<=>(x+1)(x-1)[x2(x2-9)-4(x2-9)]=0
<=>(x-1)(x+1)(x2-9)(x2-4)=0
<=>(x-1)(x+1)(x+3)(x-3)(x+2)(x-2)=0
<=>x\(\in\){-3;-2;-1;1;2;3}
phù.mệt
\(x^4+4=\left(x^4+4x^2+4\right)-4x^2=\left(x^2+2\right)^2-4x^2=\left(x^2-2x+2\right)\left(x^2+2x+2\right)\)
\(4x^4+y^4=\left(4x^4+y^4+4x^2y^2\right)-4x^2y^2\)
\(=\left(2x^2+y^2\right)^2-4x^2y^2=\left(2x^2-2xy+y^2\right)\left(2x^2+2xy+y^2\right)\)